(untitled) (Journal of the College of Education for Women, 2019)
This paper deals with assessment and focuses on ‘rubric’ which has stemmedlargely from a growing concern about the inadequacy of information provided bymost present–day assessment. Rubrics have led to a shift in emphasis from labellingand grading to diagnosis and evaluation, and hence a shift from norm to criterionreferencing as the basis for evaluating students’ performances. The present paperattempts to answer the following questions and eventually presents some examples ofrubrics.1 What is a rubric?2 Why is a rubric used?3 How is a rubric created?